Social Hierarchy and Linguistic Anxiety: A Quantitative Analysis of Arabic Speaking Barriers Among Indonesian Students in an Immersion Environment - Muhammad Hizqil Waffa; Dhimas Ilham Willian; Awaluddin Rabbany (STAI Syaichona Moh. Cholil Bangkalan, 2026)
Speaking skills (Maharah al-Kalam) are a vital component in foreign language acquisition; however, they are often hindered by psychological factors, particularly Foreign Language Anxiety (FLA). This study aims to investigate the level of Arabic language anxiety among students of Universitas Darussalam Gontor, with a focus on the influence of interlocutor hierarchy: lecturers, seniors, and peers. This research employs a descriptive quantitative design involving 77 students of the Arabic Language Education Program as respondents, using a questionnaire as the research instrument. The findings indicate that students generally experience high levels of anxiety across all interaction contexts, with a clear hierarchical pattern. Interaction with lecturers triggers the highest level of anxiety (Mean: 13.21), influenced by fear of academic evaluation. Interaction with seniors ranks second (Mean: 13.10), psychologically influenced by the internalization of the cultural value of ta’zhim, which refers to deep respect for seniors/teachers and may create pressure to perform perfectly as well as fear of making mistakes. Meanwhile, interaction with peers shows the lowest level of anxiety (Mean: 12.74), although it still falls within the high category due to social pressure and concerns about negative judgment, such as being labeled “showing off” or “acting smart.” This study concludes that Arabic language anxiety in the pesantren context is not only derived from individual factors but is also significantly influenced by social hierarchical structures. Therefore, this research contributes to the development of pedagogical communication in Arabic language learning, particularly in designing adaptive and socially sensitive communication strategies to reduce language anxiety.